Application of MULTIMEDIA Powerpoint Assisted Learning to Improve Learning Outcomes of Knowledge of the function of Fracture Machine Parts - Prastiyo pras; Muhammad Khumaedi; Kriswanto (Universitas Negeri Semarang, 2025)
The purpose of the research conducted to determine the effect of using PowerPoint multimedia on improving student learning outcomes in the subject of milling machine parts at SMK IPT Karangpanas. The background of this research is based on poor student learning outcomes, which are below the Graduation Threshold Value (KKM). Before conducting research, the feasibility of media and material was tested by experts with a percentage of 83% so that the material and media were suitable for use. The method used is quantitative experimental research with a two-group pre-test and post-test experimental model. Samples from two XI classes were taken randomly, with one experimental class and the other as a control class. Data were collected through questions in the form of pretest and posttest, and analysed using normality test, paired sample t-test, independent sample t-test, and N-Gain analysis. Results showed a significant improvement in learning outcomes in the experimental class compared to the control class, with a higher mean posttest score. The independent sample t-test showed significance <0.001, and the mean N-Gain of 0.4713 was classified as moderate. Thus, the use of PowerPoint multimedia was proven effective in improving students' learning outcomes.